School-Based Management in Improving The Quality of Education Through Communication and Information Management - Sebayang, Yulvitriyani Br; Sitanggang, Mery Sulianty H.; Damanik, Evo M.T; Hutagalung, Vera Kristina; Pemayun, I Dewa Gede Ari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The primary role of education is to enhance human resource quality through both governmental and non-governmental institutions. One proposed solution is School-Based Management (SBM), which leverages resource management to improve education quality via effective information and communication management. Schools are granted direct authority over both internal and external services. However, current information and communication management systems in schools have not significantly advanced education quality. In some cases, these systems have even impeded the creativity of educational units. For SBM to be effectively implemented, the role of the principal as a school leader is crucial, ensuring good information and communication management with all school members. This qualitative descriptive study collected data from online literature and relevant accredited journals. The findings suggest that well-managed SBM can enhance education quality through improved planning, organization, implementation, and evaluation